2021
DOI: 10.3390/cancers13164199
|View full text |Cite
|
Sign up to set email alerts
|

Selective Targeting of Class I Histone Deacetylases in a Model of Human Osteosarcoma

Abstract: Dysregulation of histone deacetylases (HDACs) is associated with the pathogenesis of human osteosarcoma, which may present an epigenetic vulnerability as well as a therapeutic target. Domatinostat (4SC-202) is a next-generation class I HDAC inhibitor that is currently being used in clinical research for certain cancers, but its impact on human osteosarcoma has yet to be explored. In this study, we report that 4SC-202 inhibits osteosarcoma cell growth in vitro and in vivo. By analyzing cell function in vitro, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 132 publications
1
4
0
Order By: Relevance
“…Remarkably, domatinostat treatment caused a dramatic increase in the sub-G1 population in GS-Y01 and GS-Y03, suggesting that domatinostat induced massive DNA fragmentation in these GSCs. Notably, while domatinostat caused a significant, though not as pronounced as in GS-Y01 and GS-Y03, increase in the sub-G1 population in TGS01, it also increased the G2/M population at the same time, in line with earlier reports that domatinostat blocked cell cycle progression at the G2/M transition in human cancer cells [ 14 , 15 , 16 ]. These results suggested that domatinostat may induce either DNA fragmentation in GSCs or cell cycle arrest at the G2/M border in intact GSCs.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Remarkably, domatinostat treatment caused a dramatic increase in the sub-G1 population in GS-Y01 and GS-Y03, suggesting that domatinostat induced massive DNA fragmentation in these GSCs. Notably, while domatinostat caused a significant, though not as pronounced as in GS-Y01 and GS-Y03, increase in the sub-G1 population in TGS01, it also increased the G2/M population at the same time, in line with earlier reports that domatinostat blocked cell cycle progression at the G2/M transition in human cancer cells [ 14 , 15 , 16 ]. These results suggested that domatinostat may induce either DNA fragmentation in GSCs or cell cycle arrest at the G2/M border in intact GSCs.…”
Section: Resultssupporting
confidence: 90%
“…With the increasing interest in HDAC inhibitors as potential cancer therapeutics, the anti-cancer activity of domatinostat, a novel class I-selective HDAC inhibitor, has been actively explored in the past several years and has been demonstrated in cancer cells from solid tumors as well as hematological malignancies. Interestingly, while earlier studies tested domatinostat mostly using conventional cancer cell lines [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], focus has been directed to its effects on CSCs in recent studies [ 21 , 22 , 23 , 24 ]. The results of the recent studies suggested the possibility that CSCs are the favored target of domatinostat, yet this possibility has not been formally tested and therefore remains to be demonstrated conclusively.…”
Section: Discussionmentioning
confidence: 99%
“…Domatinostat is a small molecule identified and characterized as a selective inhibitor of class I HDACs and has shown anti-cancer activities in vitro and in vivo against a variety of malignancies, both hematological and non-hematological, in preclinical studies [ 12 , 26 , 27 ]. Importantly, a phase 1 study conducted in 24 patients with treatment-refractory, advanced hematological malignancies demonstrated not only acceptable tolerability and safety of domatinostat but also promising signs of anti-tumor activity, with one patient achieving a complete response, another achieving a partial response, and 18 having stable disease [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in osteosarcoma, RNA-sequencing data suggested that SOX2 is underexpressed in 4SC-202-treated cells [ 38 ]. Here, in a 3D-scaffold model [ 13 ], the population of cells that express stem-like characteristics is small in the 4T1 TNBC model; about 5% of the total 4T1 population grown in the 3D scaffolds revealed a distinct CSC profile (CD44 high /CD24 low ), which significantly decreased after 4SC-202 treatment ( Figure 6 b,c).…”
Section: Discussionmentioning
confidence: 99%